2022
DOI: 10.2147/prbm.s246056
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral and Cognitive Remediation Strategies for Managing Co-Occurring Anorexia Nervosa and Elevated Autism Spectrum Traits

Abstract: Anorexia nervosa (AN) is a potentially severe eating disorder whose core characteristics include energy intake restriction leading to low body weight. Autism spectrum disorder (ASD) is a developmental disorder characterized by deficits in social interaction and communication as well as repetitive, stereotyped behavior and interests. Both high ASD traits and diagnosed ASD are overrepresented among individuals with AN, and AN and ASD appear to share certain neurocognitive features. These features are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Thus far, few treatment adaptations have been introduced to better serve autistic ED patients ( 55 57 ). A recent review synthesized findings from nine studies exploring various ways to adapt interventions based on cognitive remediation therapy (CRT), emotion skills training and cognitive behavioral therapy (CBT) to better suit the needs of autistic ED patients ( 58 ). The authors also reported that autistic ED patients, or those with high levels of autistic features, may be less likely to benefit from standard interventions, which frequently focus on altering the autistic social and cognitive processing styles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, few treatment adaptations have been introduced to better serve autistic ED patients ( 55 57 ). A recent review synthesized findings from nine studies exploring various ways to adapt interventions based on cognitive remediation therapy (CRT), emotion skills training and cognitive behavioral therapy (CBT) to better suit the needs of autistic ED patients ( 58 ). The authors also reported that autistic ED patients, or those with high levels of autistic features, may be less likely to benefit from standard interventions, which frequently focus on altering the autistic social and cognitive processing styles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, few treatment adaptations have been introduced to better serve autistic ED patients Tchanturia et al, 2021;Treasure et al, 2019). A recent review synthesised findings from nine studies exploring various ways to adapt interventions based on cognitive remediation therapy (CRT), emotion skills training and cognitive behavioural therapy (CBT) to better suit the needs of autistic ED patients (Saure et al, 2022). The authors also reported that autistic ED patients, or those with high levels of autistic traits, may be less likely to standard interventions, which frequently focus on altering the autistic social and cognitive processing styles.…”
Section: Resultsmentioning
confidence: 99%
“…Even though research into the effectiveness of recommended eating disorder treatments of autistic women with an eating disorder are still lacking, some qualitative studies have reported that in some autistic women, ‘traditional’ eating disorder motivations, such as a desire to lose weight or a low self-esteem because of body image issues were less relevant in the development of the eating disorder than other motivations, such as a need for control, sensory sensitivities, or organisational problems around cooking and food shopping or the eating disorder as a special interest [98]. Another recent narrative review has reported that autistic individuals or individuals with high autistic traits and anorexia nervosa seem to benefit less from cognitive remediation therapy (CRT) and cognitive remediation therapy and emotional skills training (CREST) [100 ▪ ]. The authors argue that this could possibly be linked to autistic traits such as difficulties in social cognition and emotion processing, cognitive inflexibility and sensory processing.…”
Section: Impact Of Autism On Eating Disordersmentioning
confidence: 99%